Perspectives on the quality and utility of letters conforming to the AAIM guidelines - Williams, Christopher (J Community Hosp Intern Med Perspect, 2021)
Background Standardized letters of recommendation (SLOR) have become common features of the medical school to residency transition. Research has shown many advantages over the narrative letter of recommendation including improved letter-writing efficiency, ease of interpretation, and improved reliability as performance predictors. Currently, at least four specialties require fellowship SLORs. Internal medicine adopted its SLOR in 2017. Previous research showed fellowship program directors’ satisfaction with the 2017 guidelines. Little is known about residency program directors’ acceptance and adherence to the guidelines. Objectives The study sought to assess the adoption rate of each component, barriers to adoption, time commitment, and alignment with intended goals of the guidelines. Methods Anonymous survey links were posted to an internal medicine discussion forum prior to the guidelines in spring 2017 and twice following the guidelines in fall 2018 and winter 2019. Two-sample tests of proportions were used to compare respondent characteristics with known survey population data. Pre- and post-survey comparisons were assessed for statistical significance with Pearson chi-squared statistic. Results The response rate varied from 30% to 35% for each survey period. Medical knowledge, patient care, interpersonal and communication skills, professionalism, and scholarly activity were reported frequently (>96%) at baseline. Inclusion of residency program characteristics, systems-based practice, practice-based learning and improvement, and skills sought to master increased over the study period. Conclusions The new guidelines improved uniform reporting of all core competency data. Overall, the gains were modest, as many pre-survey respondents reported high rates of including components within the guidelines.